Sustainability policy hastening the transition to a cleaner economy - Cohen, Steven 1953-; Eimicke, William B.; Miller, Alison (Jossey-Bass, 2015)
A complete guide to sustainability policy at the federal, state, and local levels Sustainability Policy: Hastening the Transition to a Cleaner Economy is a fundamental guide for public sector professionals new to sustainability policy development, implementation, strategy, and practice. Featuring detailed cases highlighting innovative sustainability initiatives, this book explores the elements that constitute effective policy, and the factors that can help or hinder implementation and adoption. Readers gain insight into policies in effect at the federal, state, and local levels, in the areas o